The Loss of Symbolic Imagination and the Decline of Christian Practice: A Blondelian Perspective - Doherty, Cathal (Theology today, 2026)
The contemporary decline in Christian church-going and sacramental participation is due in part to the legacy of the Enlightenment, which valorizes the life of the mind over actual practice, a distortion due to a conceptualism of human action, widespread in Western thought, that sees in human action the mere execution of ideas. From here, it is a short step to the willful blindness that restricts our action to the execution of exclusively human ideas and concepts, to the exclusion of the divine, quietly repudiating the claims of orthodox Christian revelation that the divine intention is symbolically realized for us in a true positive revelation of historical particulars (the so-called “scandal of particularity”), including the words of scripture and sacrament. This conceptualism, therefore, fosters the loss of the “symbolic imagination” - our ability or willingness to see God's hand at work through the sensory signs of human experience - in favor of an implicit “doctrine of immanence,” that restricts human action to what human beings can will or desire for themselves, with no reference at all to the divine intention as expressed in the sensory signs of revelation. Without the symbolic imagination, the words of scripture and sacrament are kept within the bounds of what appears reasonable and rational to us, repudiating any true intervention of the divine assistance. This eclipse of “symbolic imagination” is the common cause behind the decline of religious practice, and the resistance to scripture as occasion of grace, as exhibitive words of God, not simply words about God. Ultimately, our interpretation of the “words” of scripture and sacrament, is the symbol in our human finitude for the infinitude of grace, as unmerited gift. As truly revealed, the sensory signs of revealed practice and scripture speak to us something of the divine mind, not merely human ideas.